2023
DOI: 10.3390/ijgi12050180
|View full text |Cite
|
Sign up to set email alerts
|

GIS Analysis of Adequate Accessibility to Public Transportation in Metropolitan Areas

Abstract: The public transport system plays an important role in a city as it moves people from one place to another efficiently and economically. The public transport network must be organized in a way that will cover as many places and as much of the population as possible, and support the city’s growth. As one of Australia’s largest capital cities, Melbourne is growing and expanding its metropolitan area to reflect the growth in population and an increased number of activities. To date, little research has been condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…The development of the process flow was inspired from [21]. The first stage is setting up data to make them ready for analysis by loading, cleaning, and preprocessing them in the desired format.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the process flow was inspired from [21]. The first stage is setting up data to make them ready for analysis by loading, cleaning, and preprocessing them in the desired format.…”
Section: Methodsmentioning
confidence: 99%
“…The tool identified that the outer suburbs and suburbs with lower population densities of London faced accessibility challenges. Alamri et al [21] measured the accessibility and performance of the public transport system of Melbourne, Australia, using the parameter of spatial blank spots, that is, those residential regions where people do not have access to public transport stops. The paper also established the variability of services by different times (daylight hours on weekdays, evenings, nights, weekends, or 24 h) with the area of LGA and its population densities, and established that LGAs with high population densities had better coverage and access to public transport while larger LGAs tended to have a higher share of blank spots.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ref. [18] investigated methods used to determine the ease with which the residents in the metropolitan area of Melbourne (Australia) can access public transportation. This involves factors such as distance to public transport stops, travel time using public transport, and regularity of service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This distance is usually around 400-800 m. It must be noted that these distances are general guidelines and individual circumstances may vary. Factors such as local climate, topography, and the availability of convenient pedestrian routes can also affect optimal walking distances to parks [17][18][19]. Therefore, in this research, we adopt 500 m as an acceptable walking distance to public parks.…”
Section: Introductionmentioning
confidence: 99%